Nb‐Doped Hematite Nanorods for Efficient Solar Water Splitting: Electronic Structure Evolution versus Morphology Alteration. Issue 7 (1st April 2016) - Fu, Yanming; Dong, Chung‐Li; Lee, Wan‐Yi; Chen, Jie; Guo, Penghui; Zhao, Liang; Shen, Shaohua
Abstract: In this study, Nb‐doped α‐Fe2 O3 nanorod photoanodes were prepared via a facile solution‐based process by directly adding NbCl5 in the aqueous solution. The morphology and electronic structure of Nb‐doped α‐Fe2 O3 films depended strongly on the dopant concentrations. Compared with the undoped sample, the optimal Nb‐doped α‐Fe2 O3 film showed an approximately 4‐fold photocurrent increase under solar light at 1.0 V versus Ag/AgCl, and the incident photon‐to‐current conversion efficiency was increased by 2.5 times, reaching 13.7 % at 350 nm and 1.23 V versus RHE. The enhancement in PEC activity, as induced by moderate Nb doping, was attributed to the increased charge carrier density for promoted charge transfer ability as well as the smaller nanorod diameter for shortened charge transfer distance. However, superfluous Nb dopants would destroy the nanorod structure and greatly reduce the thickness of α‐Fe2 O3 films, leading to poor optical absorption and thus decreased photoelectrochemical performance. Abstract : Divide and conquer : Remarkable enhancement in solar water splitting performance was achieved over α‐Fe2 O3 nanorods by Nb doping, attributed to the improved charge transfer ability and the shortened charge migration distance. The film thickness was maintained for good optical absorption.